2016
DOI: 10.21474/ijar01/1828
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of Adsorption Process of Chromium Ions From Aqueous Solution.

Abstract: The adsorption efficiency of granular activated carbon was investigated for removal of Cr(VI) ions in a lab scale fluidised bed reactor. The effect of various parameters like pH, contact time and initial metal ion concentration on adsorption process were investigated. More adsorption was observed at lower pH and optimum pH was found to be 3.0.The equilibrium time was observed at 420 min. With the increase in initial Cr(VI) ion concentration, the percentage adsorption decreases while the adsorption capacity (q … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
10
0
2
Order By: Relevance
“…Furthermore, much literature investigated cadmium accumulation's adverse effects on lung tissues and the related respiratory problems, as well as its effect on immunity suppression [15]. Consequently, developing processes for removing cadmium from industrial wastewaters and drinking water becomes essential [16]. According to FAO/WHO permitted pollution levels, the limit of cadmium should be less than 0.005 mg/l.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, much literature investigated cadmium accumulation's adverse effects on lung tissues and the related respiratory problems, as well as its effect on immunity suppression [15]. Consequently, developing processes for removing cadmium from industrial wastewaters and drinking water becomes essential [16]. According to FAO/WHO permitted pollution levels, the limit of cadmium should be less than 0.005 mg/l.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Cu has been reported to have adverse effects on human health. These include mental disorders, anemia, arthritis/rheumatoid arthritis, hypertension, and liver enlargement (Lakherwal, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was reported that nanomaterials have appropriate adsorption surfaces that possess unique characteristics vis-à-vis a very high surface-areato-volume ratio. All of these advantages give a tremendous driving force for diffusion, especially at high temperatures [9] .…”
Section: Introductionmentioning
confidence: 99%
“…It was known to cause harm to vital human organs such as the lungs, kidney, liver, reproductive system, brain and basic cellular processes. Soaring knowledge of the ecological effect of lead (Pb 2+ ) ions has provoked calls for decontamination of polluted water preceding release into waters bodies (Lakherwal, 2014;Singh &Gupta, 2016 andAbdel-Raouf &Abdul-Raheim, 2017).…”
Section: Introductionmentioning
confidence: 99%